Estudo microbiológico comparativo entre sabão de clorexidina 2% e um novo sabão antisséptico para lavagem pré-operatória das mãos - Monnazzi, Marcelo Silva [UNESP]; Messaddeq, Younès [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Pelaes, Silvana aparecida Rodrigues Camargo [UNESP]; Saska, Sybele; Negrini, Thais de Cássia; Gabrielli, Mario Francisco Real [UNESP] (My University, 2012)
Objective: To evaluate, by means of a microbiologic study, two kinds of soaps suggested by surgeons for presurgical handwashing, comparing a well-known antibacterial soap with a new soap formulated from vegetable oils. Materials and methods: Ten volunteers performed handwashing according to previously established protocols for routine antisepsis in operating rooms using 3 different soaps: a common, commercially marketed soap, serving as the control group (Group 1), with no antibacterial characteristics; a soap with 2% chlorhexidine (Group II); and a new soap formulated from vegetable oils at a concentration of 20%, known as surfactant, which was designed by the Chemistry Institute (Unesp/Araraquara – Grupo de Materiais Fotônicos) (Group III). The microbiological samples were collected immediately before and after handwashing and one hour later with the volunteer wearing surgical gloves. Results: ANOVA revealed that the following significant differences are found in the number of bacterial colonies: between soap types (a smaller number of colonies in the Group II soap), between periods (reduction in the number of colonies in the Group II soap), and the significant effect of the soap versus time interaction. Conclusion: The 2% chlorhexidine soap performed better in reducing the number of bacterial colonies on the hands immediately after handwashing and after one hour with the use of surgical gloves, when compared to the 20% surfactant soap.

Objetivos: avaliar, por meio de estudo microbiológico, dois tipos de sabão propostos para a lavagem das mãos na preparação dos cirurgiões no tempo pré-operatório; comparando um sabão com potência antibacteriana já conhecida e um novo sabão formulado a partir de óleos vegetais. Materiais e métodos: Dez voluntários fizeram a escovação das mãos, segundo protocolos pré-estabelecidos para a rotina de medidas de antissepsia em centros cirúrgicos, com 3 sabões diferentes, sendo um sabão comum (comercial) sem poder antisséptico que serviu como Grupo Controle (I), um sabão de digluconato de clorexidina a 2% (Grupo II) e um novo sabão feito a partir de óleos vegetais numa concentração de 20%, que foi desenvolvido pelo Instituto de Química Unesp/araraquara no Grupo de Materiais Fotônicos, denominado surfactante a 20% (Grupo III). antes de lavar as mãos, logo após e uma hora depois com o uso de luvas cirúrgicas, foi realizada a coleta microbiológica. Resultados: Pelos resultados da aNoVa, verificam-se as seguintes diferenças significativas para o número de colônias bacterianas: entre tipos de sabão (menor número de colônias no sabão do Grupo II), entre tempos (redução do número de colônias no sabão do Grupo II) e efeito significativo da interação sabão versus tempo. Conclusão: o sabão de digluconato de clorexidina 2% mostrou um comportamento melhor em reduzir o número de colônias bacterianas das mãos imediatamente após a lavagem e continuou sendo superior após uma hora com o uso de luvas, quando comparado ao sabão de surfactante a 20%.
Microbiological study comparing 2% chlorhexidine soap and a new antiseptic soap for preoperative handwashing
Keywords: Antisepsis; Handwashing; Soaps; Chlorhexidine; Antissepsia; Lavagem das mãos; Clorexidina